Faktor-Faktor Yang Mempengaruhi Kinerja Bidan Terhadap Cakupan PWS KIA Di Puskesmas Tigo Baleh Kota Bukittinggi Tahun 2014 - Mutia Felina, Mutia; Rulfia Desi maria, Rulfia (LPPM Universitas Prima Nusantara Bukittinggi, 2014)
Percentage coverage in health centers MRL MCH Tigo Baleh still low compared to other health centers in Bukittinggi City is 83.9%. Monitoring Local Regional Maternal and Child Health (MRL MCH) is a management tool to monitor the MCH program in a continuously working area, so that follow-up can be done quickly and accurately. This study aims to determine the factors that affect the performance of the scope of the MRL MCH midwife at the health center of Bukittinggi 2014 Tigo Baleh type of research used in this study is qualitative descriptive design and interviews. The sample in this study is the Midwife Coordinator, Head of health centers and midwives who work in health centers Baleh Tigo. Collection techniques in this study is the in-depth interviews. The results of this study showed that of the 3 respondents who work in health centers Baleh Tigo three factors, namely behavioral changes predisposing factors, enabling factors and reinforcing factors, midwives aged around 26-47 years, and all educated DIII Midwifery. For a task / future work in the village there is a very varied new 3 months while there are already quite a long time 12-14 years. Most of the midwives is a permanent employee / civil service. Mosh midwives lazy to do the recording and reporting of MRL MCH because it was too much recording and reporting to be done. Factors such as sesame amplifier midwives mutually discuss and even make statements together in community health centers. It is expected that the research institutions to conduct training on record keeping and reporting